The Development and use of Category Management practice in UK retailing - Lall, Manjit (2007)
The abolition of the Retail Price Maintenance Legislation (RPM) in 1964 had a significant impact on the UK retailing industry. Power began to shift away from the manufacturers to the retailers, who were now able to set their own pricing strategies.